2012
DOI: 10.1186/1471-2431-12-34
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of an evidence-based clinical answer format for pediatricians

Abstract: BackgroundClinicians are increasingly using electronic sources of evidence to support clinical decision-making; however, there are multiple demands on clinician time, and summarised and synthesised evidence is needed. Clinical Answers (CA) have been developed to address this need; the CA is a synthesised evidence-based summary that supports point-of-care clinical decision-making. The aim of this paper is to report on a survey used to test and improve the CA format.MethodsAn online survey was sent to pediatrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…6,10,[12][13][14][15][16] Other studies examining communication methods have highlighted parents' needs for impartial discussions about vaccines from HCPs, using patient-tailored information. [17][18][19] Much less is written about the challenges HCPs themselves face in undertaking this role. In our study, HCPs identified that patients' low vaccine education/miseducation, untimely and/or unclear vaccine information, frequently changing vaccine schedules, lack of time in consultations, lack of central patient record systems, pressure to achieve vaccination targets, and vaccine cost, all highly impacted their efficiency and enthusiasm.…”
Section: Discussionmentioning
confidence: 99%
“…6,10,[12][13][14][15][16] Other studies examining communication methods have highlighted parents' needs for impartial discussions about vaccines from HCPs, using patient-tailored information. [17][18][19] Much less is written about the challenges HCPs themselves face in undertaking this role. In our study, HCPs identified that patients' low vaccine education/miseducation, untimely and/or unclear vaccine information, frequently changing vaccine schedules, lack of time in consultations, lack of central patient record systems, pressure to achieve vaccination targets, and vaccine cost, all highly impacted their efficiency and enthusiasm.…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus (RV) infection is the primary cause of viral acute gastroenteritis (GE) in infants and children <5 years old. 1,2 It is estimated that by the age of 5 years, nearly every child will have had at least one episode of rotavirus gastroenteritis (RVGE). 3 Although maintaining good hygiene like handwashing, sanitation along with exclusive breastfeeding for 6 months, vitamin A supplementation and safe drinking water are essential to prevent the spread of infections, RV vaccination has proven to be the most effective approach to protect children against RVGE disease.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, poor communication and lack of in-depth knowledge about immunisation can contribute to rejection of vaccinations, especially for vaccine hesitant parents. 1 Research shows that parents' decision-making about childhood vaccines begins during pregnancy. 2 Pregnant women are also now required to consider recommended antenatal vaccines.…”
mentioning
confidence: 99%